The Emerging Role of Oyster Mushrooms as a Functional Food for Complementary Cancer Therapy - Priya Lakshmi Sreedharan; Malu Kishorkumar; Elke Gabriel Neumann; Shyam S. Kurup (Foods, 2025)
The importance of functional food’s role in human nutrition as well as in the prevention of diseases, especially the treatment of chronic diseases like cancer, is an innovative field of research. Based on the studies regarding the antioxidant potential of oyster mushroom extract, it is evident that it has anticancer properties. The current article reviews the health benefits of edible oyster-mushroom-derived bioactive compounds, and how they specifically activate or regulate the immune system by affecting the maturation, differentiation, and proliferation of immune cells, thereby inhibiting cancer cell metastasis and growth. Mushrooms show anticancer potential by regulating a single molecule of a specific signaling pathway or by having multiple targets in the same or different signaling pathways. In addition, the prebiotic effects of mushrooms could enhance quality of life during and after cancer therapy by recovering the intestinal microbiota. More clinical research on oyster mushrooms needs to be conducted, and future studies should investigate the preventive aspects, which aid in reducing the rate of cancer occurrence, and the positive impact in cancer patients to prove that oyster mushrooms are preventive as a functional food as well as a curing dietary supplement for cancer patients.